Wood Physical and Mechanical Properties of Natural Dipterocarpus costatus C.F.Gaertn. in Borikhamxay Province, Lao PDR - Bouaphavong, Douangta; Saikor, Louxiong; Boupha, Latsamy; Chanthavong, Houngphet; Soukanya, Kongkeo (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
Physical and mechanical property of Dipterocarpus costatus C.F.Gaertn are significant point on wood industry in Laos and international market. The aim of this study focuses on physical and mechanical properties from natural forest and selected three trees of 50, 60 and 75 cm diameter for experiment. The testing was followed on ASTM D143 ASTM (2013) method and data analysis used One-way ANOVA in variation different significant of between tree, height and inner to outer wood. As the result showed that wood moisture content in 12% the wood density was 768.29 kg/m3, shrinkage of tangential was 5.54%, radian was 2.53%, length was 0.48% and volume was 8.30%. The mechanical property was 118.29 MPa of MOR, 13,450.40 MPa of MOE, 13.53 MPa of compression, 29.27 MPa of shearing. The variable significant (different diameter) between group of trees was density, tangential shrinkage, length shrinkage, volume shrinkage, specific gravity, MOR, MOE, hardness and shearing (P-value<0.05). The height variable significant of tree was density, specific gravity, compression and shearing (P-value<0.05). The variable inner to outer wood significant different was only radian shrinkage (P-value<0.05).